2022
DOI: 10.1101/2022.12.23.521761
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emerging variants of SARS-CoV-2 NSP10 highlight strong functional conservation of its binding to two non-structural proteins, NSP14 and NSP16

Abstract: The coronavirus SARS-CoV-2 protects its RNA from being recognized by host immune responses by methylation of its 5' end, also known as capping. This process is carried out by two enzymes, non-structural protein 16 (NSP16) containing 2'-O-methyltransferase and NSP14 through its N7 methyltransferase activity, which are essential for the replication of the viral genome as well as evading the host's innate immunity. NSP10 acts as a crucial cofactor and stimulator of NSP14 and NSP16. To further understand the role … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
2
2
0
Order By: Relevance
“…In contrast with this, ORF10, NSP7, and NSP10 were the lowest mutating in all the three periods for all the countries taken into consideration. This was in line with previous studies where they were found to be conserved within the SARS-CoV-2 genome with few or no mutations ( 47 , 58 60 ).…”
Section: Resultssupporting
confidence: 93%
“…In contrast with this, ORF10, NSP7, and NSP10 were the lowest mutating in all the three periods for all the countries taken into consideration. This was in line with previous studies where they were found to be conserved within the SARS-CoV-2 genome with few or no mutations ( 47 , 58 60 ).…”
Section: Resultssupporting
confidence: 93%
“…In contrast with this, ORF10, NSP7 and NSP10 were the lowest mutating in all the three periods for all the countries taken into consideration. This was in line with previous studies where they were found to be conserved within the SARS-CoV-2 genome with few or no mutations (69,(80)(81)(82).…”
Section: Rise Of % Mutations Rates In S N Nsp3 and Nsp4 In The Post-v...supporting
confidence: 93%
“…NSP10 ω is increased maximally in delta (ω = 0.68) but decreased in alpha (ω = 0.00) and omicron (ω = 0.00) ( Figure 5 c, Table 1 ), indicating that some of the delta-specific severity could be attributed to NSP10 mutations. Further, no significant mutations are detected in NSP10 in omicron but D119-, T12I, T102I and A104V in delta stabilize the effect on binding NSP10 with NSP14 and NSP16 [ 61 ]. This binding stabilization is implicated in impairing viral host immune responses, resulting in increased viral pathogenesis [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Omicron showed an insufficient or delayed IFN response without total suppression, which are attributed to having a milder phenotype than delta [ 88 ]. Delta-specific mutations in ORF8 (D119-), ORF5 (I82T), NSP10 (L133F), NSP16 (K160R and G77R), NSP5 (G15S and K90R), ORF6 (G15S and K90R), ORF7A (P45L, V82A and T120I) act as IFN antagonists and are associated with severe COVID-19 illness [ 30 , 61 , 65 , 67 ]. Delta also showed the highest peak of ω in some non-immune related genes ( ORF5 , NSP14 , and NSP16 ) involved in viral assembly, packaging, and transport.…”
Section: Discussionmentioning
confidence: 99%